The right to life - Tomuschat, Christian; Lagrange, Evelyne; Oeter, Stefan (Martinus Nijhoff Publishers, 2010)
The right to life stands at the heart of human rights protection. Individuals cannot enjoy any of the rights guaranteed to them unless their physical existence is ensured. All human rights instrument list the right to life as the first one of their safeguards. Nonetheless, in many situations human life finds itself under structural threat. Although obligated by law to protect the right to life, State authorities time and again engage in deliberate acts of killing. Fortunately, international review bodies have devised many imaginative counter-strategies. Another one of those structural threats.